Dopaminergic drug effects during reversal learning depend on anatomical connections between the orbitofrontal cortex and the amygdala - van der Schaaf, Marieke E.; Zwiers, Marcel P.; van Schouwenburg, Martine R.; Geurts, Dirk E.; Schellekens, Arnt F.; Buitelaar, Jan K.; Verkes, Robbert Jan; Cools, Roshan (Frontiers in Neuroscience, 2013)
Dopamine in the striatum is known to be important for reversal learning. However, the striatum does not act in isolation and reversal learning is also well accepted to depend on the orbitofrontal cortex (OFC) and the amygdala. Here we assessed whether dopaminergic drug effects on human striatal BOLD signalling during reversal learning is associated with anatomical connectivity in an orbitofrontal-limbic-striatal network, as measured with diffusion tensor imaging. By using a fibre-based approach, we demonstrate that dopaminergic drug effects on striatal BOLD signal varied as a function of fractional anisotropy (FA) in a pathway connecting the OFC with the amygdala. Moreover, our experimental design allowed us to establish that these white-matter dependent drug effects were mediated via D2 receptors. Thus, white matter dependent effects of the D2 receptor agonist bromocriptine on striatal BOLD signal were abolished by co-administration with the D2 receptor antagonist sulpiride. These data provide fundamental insight into the mechanism of action of dopaminergic drug effects during reversal learning. In addition, they may have important clinical implications by suggesting that white matter integrity can help predict dopaminergic drug effects on brain function, ultimately contributing to individual tailoring of dopaminergic drug treatment strategies in psychiatry.